Teaching an old ‘doc’ new tricks for algal biotechnology: Strategic filter use enables multi-scale fluorescent protein signal detection - Gutiérrez, Sergio; Wellman, Gordon B.; Lauersen, Kyle J. (Frontiers in Bioengineering and Biotechnology, 2022)
Fluorescent proteins (FPs) are powerful reporters with a broad range of applications in gene expression and subcellular localization. High-throughput screening is often required to identify individual transformed cell lines in organisms that favor non-homologous-end-joining integration of transgenes into genomes, like in the model green microalga Chlamydomonas reinhardtii. Strategic transgene design, including genetic fusion of transgenes to FPs, and strain domestication have aided engineering efforts in this host but have not removed the need for screening large numbers of transformants to identify those with robust transgene expression levels. FPs facilitate transformant screening by providing a visual signal indicating transgene expression. However, limited combinations of FPs have been described in alga and inherent background fluorescence from cell pigments can hinder FP detection efforts depending on available infrastructure. Here, an updated set of algal nuclear genome-domesticated plasmid parts for seven FPs and six epitope tags were generated and tested in C. reinhardtii. Strategic filter selection was found to enable detection of up to 5 independent FPs signals from cyan to far-red separately from inherent chlorophyll fluorescence in live algae at the agar plate-level and also in protein electrophoresis gels. This work presents technical advances for algal engineering that can assist reporter detection efforts in other photosynthetic host cells or organisms with inherent background fluorescence.